2021
DOI: 10.2196/26387
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Breaks in Sedentary Behavior of Older Adults Immediately After Receiving Personalized Haptic Feedback: Intervention Study

Abstract: Background “Push” components of mobile health interventions may be promising to create conscious awareness of habitual sedentary behavior; however, the effect of these components on the near-time, proximal outcome, being breaks in sedentary behavior immediately after receiving a push notification, is still unknown, especially in older adults. Objective The aims of this study are to examine if older adults break their sedentary behavior immediately after… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The results of this study that demonstrated a majority of haptic vibrations, especially those in the morning, did not result in a break in the sedentary behavior of older adults. As such, simply bringing habitual sedentary behavior into conscious awareness seems to be insufficient to target sedentary behavior [ 60 ]. In turn, O’Caoimh et al (2018) [ 47 ] found that health literacy and ICT literacy (eHealth) were useful in helping older people to access such services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study that demonstrated a majority of haptic vibrations, especially those in the morning, did not result in a break in the sedentary behavior of older adults. As such, simply bringing habitual sedentary behavior into conscious awareness seems to be insufficient to target sedentary behavior [ 60 ]. In turn, O’Caoimh et al (2018) [ 47 ] found that health literacy and ICT literacy (eHealth) were useful in helping older people to access such services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the healthy aging perspective includes the physical, social, and cognitive domains, as well as healthy environments to promote healthy lifestyles, well-being, and social participation [ 25 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, older adults already indicated that they were not eager to interrupt/reduce their television time, which is a typical evening activity [ 53 ]. Indeed, a recent study, investigating breaks in older adults’ sedentary behavior immediately after receiving personalized haptic feedback, showed that older adults were most likely to interrupt their sedentary behavior in the afternoon [ 54 ]. To draw firm conclusions on the optimal time period to provide sedentary behavior support, future researchers are recommended to combine data collection on when older adults are susceptible to sedentary behavior, and when older adults are willing to receive, process and utilize support [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…To break the habit of SB, several studies suggested that older adults need to become aware about the automaticity of their behavior 39,46,99 . Providing feedback on behavior and stimulating older adults to monitor their own behavior are frequently used BCT's that might lead to an increased awareness 39,40,45,49,56,62,84,88 . However, only bringing habitual behavior into conscious awareness seems insufficient to generate behavior change 39,49,57 .…”
Section: Under What Types Of Motivation Do Which Mechanisms Lead To C...mentioning
confidence: 99%
“…reading the paper or eating lunch) 113 . As a result, interventions that prompt people to interrupt their SB actually ask people to interrupt achieving their goals which might lead to frustrations 113 and negative intervention outcomes 49,62,75,79 . In order to make the most out of the mechanism of prompting, it is crucial to examen the most appropriate timing to provide a prompt to interrupt SB 40,113 .…”
Section: Under What Types Of Motivation Do Which Mechanisms Lead To C...mentioning
confidence: 99%